Development of magnetic materials for cobalt titanium oxide using mechanical milling and the characterization methods - Imastuti; Adi Wisnu Ari; Mutmainnah Mutmainnah; Haziza Elsa Putri; Raditya Faradina Pratiwi; Atmadi (FoundAE, 2023)
In the synthesis of magnetic materials for absorbing radar waves, it is necessary to have a base material that has unique magnetic properties that can reach the broadband characteristics of radar frequencies. Cobalt titanium oxide is synthesized using mechanical milling. The phase formed by calcination at 1000â„ƒ with a holding time of 5 hours. Sample characterization was carried out by XRD, VSM and VNA. Based on the research results, it was found that the material obtained had semiparamagnetic properties. From the SEM measurements, it is reactive to the sintering temperature. Radar wave absorption measured by VNA shows that cobalt titanium oxide shows a value with uniform absorption in the X-band wave.